PENINGKATAN KINERJA PERGURUAN TINGGI SWASTA MELALUI PENERAPAN KNOWLEDGE MANAGEMENT DAN PENGUATAN BUDAYA ORGANISASI - MASDUKI (Coopetition : Jurnal Ilmiah Manajemen, 2019)
The application of knowledge management and the strengthening of organizational culture are important strengths in improving the performance of private tertiary institutions. This study aims to determine the effect of knowledge management on the performance of Private Universities through strengthening organizational culture. The population used is the Permanent Lecturer at Majalengka University. Samples were taken through quota sampling. Data analysis method used in this study is path analysis. The results showed that knowledge management directly had a significant and positive effect on organizational culture and performance of private tertiary institutions. Organizational culture is able to strengthen the influence of knowledge management on the performance of private tertiary institutions.